Pelatihan Eco-Entrepreneurship Berbasis Pemanfaatan Limbah Botol Plastik Bernilai Ekonomi bagi Mahasiswa I-CATS University College - Hanum Mukti Rahayu; Mahwar Qurbaniah; Jessika; Melanie (BALE LITERASI, 2026)
Plastic waste, particularly single-use plastic bottles, has become an environmental issue that requires serious attention because it can cause environmental pollution and ecosystem damage. This condition is also found within the environment of I-CATS University College, where the use of plastic packaging remains high but is not yet balanced by students’ awareness and skills in managing plastic waste into economically valuable products. Therefore, this community service program aimed to enhance environmental awareness, waste processing skills, and students’ entrepreneurial spirit through the implementation of eco-entrepreneurship based on the utilization of plastic bottle waste. The program was carried out in three stages: socialization and education on plastic waste management, training and hands-on assistance in transforming plastic bottles into creative products with economic value, and program evaluation through the distribution of participant response questionnaires. The program was conducted on August 9, 2025, at Surau Baitul Quddus, Kampung Pueh Sematan, Kuching, Malaysia, through a collaboration between Universitas Muhammadiyah Pontianak and I-CATS University College. The results showed that participants were able to produce various creative products such as eco-friendly bags, decorative lamps, and storage containers. The evaluation results indicated that partner responses were categorized as good to very good, particularly in terms of program suitability to partner needs, the benefits of the activities, and the increased motivation of participants in applying the knowledge and skills acquired. Thus, this eco-entrepreneurship program was considered effective in enhancing environmental awareness, creativity, skills, and students’ entrepreneurial potential based on a sustainable circular economy.